2014
DOI: 10.4046/trd.2014.76.5.233
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Catamenial Hemoptysis Treated by Bronchial Artery Embolization

Abstract: Catamenial hemoptysis is a rare condition, characterized by recurrent hemoptysis associated with the presence of intrapulmonary or endobronchial endometrial tissue. Therapeutic strategies proposed for intrapulmonary endometriosis with catamenial hemoptysis consist of medical treatments and surgery. Bronchial artery embolization is a well-established modality in the management of massive or recurrent hemoptysis, but has seldom been used for the treatment of catamenial hemoptysis. We report a case of catamenial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The primary goal of surgery for thoracic endometriosis is to minimize recurrence by precisely locating the lesions and completely removing them, when all other conservative measures fail. In our study, the single patient that underwent bronchial artery embolization experienced no recurrence; this is consistent with a report from another institution [ 19 ], suggesting embolization may be suitable as a first line treatment. Because of the risks of thoracic surgery, operative management should be a last resort in cases where symptoms prevail.…”
Section: Discussionsupporting
confidence: 92%
“…The primary goal of surgery for thoracic endometriosis is to minimize recurrence by precisely locating the lesions and completely removing them, when all other conservative measures fail. In our study, the single patient that underwent bronchial artery embolization experienced no recurrence; this is consistent with a report from another institution [ 19 ], suggesting embolization may be suitable as a first line treatment. Because of the risks of thoracic surgery, operative management should be a last resort in cases where symptoms prevail.…”
Section: Discussionsupporting
confidence: 92%
“…Massive hemoptysis can be caused by a variety of conditions, such as infections (mycobacterial, fungal, or bacterial), medications, cocaine, bronchitis, bronchiectasis, tumors eroding into the pulmonary vasculature, endobronchial tumors, vascular abnormalities, endometrial tissue (catamenial hemorrhage), foreign bodies, and fistulas between major arteries and the bronchial tree. [1][2][3][4][5][6][7] Its incidence is difficult to assess, as there is no unifying definition of the condition. Bronchiectasis is a common cause, accounting for 31% to 66% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Fatal hemoptysis from CH has not yet been reported but it may cause life-threatening asphyxiation. Recent studies have reported massive hemoptysis requiring bronchial embolization in CH [9,10]. In addition, recurrent hemoptysis by CH can reduce the quality of life of patients due to the associated respiratory symptoms and anxiety.…”
mentioning
confidence: 99%